EFFECTS OF THERAPEUTIC ULTRASOUND ON THE RETENTION AND MAINTENANCE OF THE ANTIOXIDANT ACTIVITY OF THE GLYCOLIC EXTRACT OF ARNICA MONTANA: AN IN VITRO STUDY - Tassinary, João Alberto Fioravante; Bianchetti, Paula; Stülp, Simone (Ciência e Natura, 2014)
http://dx.doi.org/10.5902/2179460X12587 The aim of the present study was to evaluate the retention of a glycolic extract of A. montana using a biomembrane model, and to determine the effect of therapeutic ultrasound on the antioxidant capacity of the extract. Biomembrane samples were treated in a vertical diffusion system with A. montana extract/hydrogel homogenate in the absence or presence of ultrasound (3 MHz; 1.0 W/cm2). Biomembranes that had been submitted to ultrasound for 4 and 150 min retained, respectively, 93.5 and 69.03% less of the bioactive extract than those treated with passive diffusion for similar periods, thus indicating that phonophoresis enhances permeation through the membrane. Cyclic voltammetry was employed in the determination of antioxidant activities by measurement of the amount of hydrogen peroxide neutralized by the extract. Electrochemical analysis showed that the peak current related to the reduction of hydrogen peroxide diminished when extract was present. However, treatment of the extract with ultrasound gave rise to a decrease in the antioxidant potential, as indicated by an observed increase of 27% in hydrogen peroxide concentration in comparison with untreated extract. It is concluded that, although ultrasound improves permeation of the glycolic extract of A. montana, the antioxidant activity of the preparation is diminished.